THU0094 Experimental mycoplasma fermentans infection in rheumatoid synovial fibroblasts induces m161ag expression. (1st June 2001) - Kitajima, S; Kawano, M; Mutoh, H; Koni, I; Mabuchi, H; Matsumoto, M; Seya, T
Abstract : Background: Mycoplasma fermentans (Mf) is one of the most likely of the several infectious agents which may be involved in the pathogenesis of rheumatoid arthritis (RA). Mf has been shown to induce arthritis experimentally in rabbits, and several reports have succeeded in detecting it in synovial fluids in RA patients. M161Ag is a 43-kDa surface lipoprotein of Mf, which induces cytokine production in monocytes and activates the host complement system. Objectives: The aim of this study was to investigate whether M161Ag can be induced on rheumatoid synovial fibroblasts by an Mf infected cell line in vitro . Methods: Rheumatoid synovial cells were isolated from synovial tissue specimens obtained at operation. Production of Mf infected rheumatoid synovial cells was performed using a coculture system of synovial cells and P39 (+) cells, which were Mf containing human leukaemia cell lines, for three days. PCR with mycoplasma specific primers were done to detect Mf DNA in synovial cells. M161Ag expression was evaluated by an immunohistochemical method with MK5 and MK53 monoclonal anti M161Ag antibodies, and mRNA production was also evaluated by the RT-PCR method. Results: Freshly isolated rheumatoid synovial cells were negative for Mf DNA using PCR with mycoplasma specific primers. DNA of Mf ribosomal RNA was detected in the synovial fibroblasts after coculture of synovial cells and P39 (+) cells by PCR with mycoplasma specific primers. Moreover, the expression of M161Ag was detected only on Mf infected synovial cells using the immunohistochemichal method with MK5 or MK53 monoclonal antibodies. Conclusion: Experimental in vitro Mf infection in rheumatoid synovial fibroblasts was demonstrated to induce the expression of M161Ag. The significance of this finding requires clarification in further studies. References: Matsumoto M, et al . A novel protein that participates in nonself discrimination of malignant cells by homologous complement. Nat Med. 1997;3:1266 Matsumoto M, et al. Structural and functional properties of complement-activating protein M161Ag, a Mycoplasma fermentans gene product that induces cytokine production by human monocytes. J Biol Chem. 1998;273:12407